Jobs for youth : Japan = Des emplois pour les jeunes - Organisation for Economic Co-operation and Development (OECD, 2009)
Summary and main recommendations (s. 9-19).
Keywords: työhönsijoittuminen : nuoret : Japani; työllisyys : nuoret : Japani; työvoimapolitiikka : Japani; nuoret työntekijät : Japani; työvoima : nuoret : Japani; koulutus : Japani